(untitled) (Journal of Hama University, 2020)
The research aims to identify the most important obstacles to the integration of technology in education from the point of view of the teachers of the first ring in the schools of the city of Damascus for the year 2018/2019, And study the statistical differences in the responses of respondents on the identification of obstacles to the integration of technology in education according to variables (sex - number of years of experience - educational qualification), The sample of the study reached 360 teachers. The researcher used the descriptive approach to conduct the research, In order to reach its results, the researcher designed the research tools represented by a questionnaire consisting of two axes of obstacles (physical - human), Each axis has a number of phrases, The study showed several results, the most important of which are: the degree of approval of the presence of obstacles to the integration of technology in education on the questionnaire as a whole was moderate, and on its axes. Also the degree of the presence of physical and human constraints individually was moderate, and by comparison of averages shows that the degree of presence of physical obstacles was higher than the degree of presence of human obstacles. The research found also that there is no difference in the responses of respondents to the identification of obstacles according to the sex variable, while there are differences according to the number of years of experience (in favor of years of less experience) and there are differences according to the educational qualification (in favor of the higher educational qualification).